Grain-boundary/interface structures and scatterings of ruthenium and molybdenum metallization for low-resistance interconnects - Chen, Yu-Lin; Fang, Yi-Ying; Lu, Ming-Yen; Keng, Pei Yuin; Chang, Shou-Yi (Applied surface science, 2023)
[Display omitted] •The resistivity scaling of ruthenium and molybdenum films were investigated.•The bulk resistivity of the metal films was dominated by impurities (oxygen).•The grain-boundary reflectivity was controlled by the structure coherency.•Low electronegativity promoted interface bonding but caused low permeability.•A simple methodology to predict the interface permeability was established. Ruthenium and molybdenum are of great potential to replace copper for use as the next-generation interconnect metallization. Important parameters including their intrinsic resistivity, grain-boundary reflectivity and interface permeability need to be carefully examined. Hence in this study, ruthenium and molybdenum films with various thicknesses were prepared on different substrates by physical vapor, chemical vapor and atomic layer depositions. The microstructure, chemical compositions, bonding configurations and interfacial adhesion were characterized, and the electrical resistivities with scaling was examined using the Fuchs-Sondheimer and Mayadas-Shatzkes models. Experimental results indicate that the grain-boundary reflectivity was strongly influenced by the structure coherency and impurity (oxygen) segregation. Thermal annealing facilitated defect elimination and structure recovery, lowering the intrinsic resistivity and the grain boundary reflectivity. Strong interface bonding caused serious interface diffuse scattering, and an inverse proportional relationship between interfacial adhesion strength and interface permeability was suggested, which was dominated by the electronegativity of the metals.